Effect of Furans and a Pyran on Several Quorum Sensing Factors in Ralstonia solanacearum - Gallego Cruz, Adriana María (2016)
Ralstonia solanacearum race 2 is the causative agent of Bacterial Wilt in bananas, a disease also known as Moko disease. Once this bacterium becomes established within a plant, it causes the death of its host. Currently, no treatment is available for Bacterial Wilt, and the disease is able to destroy 100% of the crops in afflicted áreas.This study investigates a non-biocidal control method for R. solanacearum that attempts to nullify the pathogenic effects of R. solanacearum by interfering with the bacteria?s Quorum Sensing (QS) communication system. The effects of several molecules on R. solanacearum growth, biofilm formation and production of acylated homoserine lactone (AHL) autoinducers were analyzed. The results suggested that, of the molecules tested, 5,6 dihydro-2(H)- pyran-2-one most effectively inhibited growth, biofilm formation and AHL production. Furfural, 3-methyl-2(5H)- furanone and methyl 2-furoate also effectively inhibited growth. These molecules affected biofilm formation in a concentration-dependent manner. In addition, 3-methyl-2(5H)-furanone and methyl 2-furoate likewise inhibited AHL production. Therefore, all of these molecules could be useful for controlling R. solanacearum.